Preceptoria no estágio curricular de nutrição : o desafio do fazer - França, Ana Patricia Tojal de (2014)
The work herein is the result of research carried out during the course of a Professional Master’s Degree Program in Health Education. It consists of a scientific article and the product of an intervention stemming from the study. Its goal was to assess the preceptorship developed in a public health nutrition internship program at an institution of higher education in the city of Maceio – AL, based on the experiences of faculty members and preceptors engaged in it. It was a qualitative approach research using a case study format. Data were collected through focus group (FG) technique and evaluated using content analysis. Separate FG sessions were carried out for faculty members and preceptors. It was noted in the results: the conceptions of the groups regarding preceptorship are controversial; the education is crippled by the weak participation of nutritionists in primary health care; working conditions in health care settings are precarious; there is poor interaction between educational institutions and health care providers; there is the need to invest in the pedagogical development of those professionals involved in preceptorship programs. The scientific article that ensued from these results discusses the aspects deemed essential for singling out preceptorship for the internship program concerned and to the product of the intervention, whose intention was to create a pedagogical tool that would stimulate critical reflective thought in those involved in health education while simultaneously meeting the demand for novel technologies to be used in professional teaching in that area. Thus, an animation video was created depicting one of the many settings in health care practice. This work led to pleasant gatherings and reflections on preceptorship and the experiences and meanings thereof; it opened windows of possibilities for new research and proclaimed the importance of strengthening classroom-workplace integration toward adequate education and the rendering of good health care services.